Petrographic and chemical characterization and carbon and nitrogen isotopic compositions of cometary IDPs and their GEMS amorphous silicates - Schulz, Birgit; Vollmer, Christian; Leitner, Jan; Keller, Lindsay P.; Ramasse, Quentin M. (Geochimica et cosmochimica acta, 2024)
GEMS (glass with embedded metal and sulfides) are the dominant carrier of amorphous silicates in anhydrous interplanetary dust particles (IDPs) and one of the most suitable materials to study early solar system processes. Amorphous silicates in 105 GEMS from eight IDPs were analyzed regarding texture and chemical composition to reassess GEMS formation theories and genetic relationships to amorphous silicate material in meteorites. Petrography of bulk IDPs was investigated to understand GEMS’ relationships to other IDP components. Furthermore, carbon and nitrogen isotopic compositions were measured. Nearly all GEMS are aggregates of several subgrains with variable amount of nanophase inclusions and different Mg- and Si-contents, while single GEMS are rare. The subgrains within aggregates are typically surrounded by one or more carbon rims with high density. The chemical compositions of GEMS amorphous silicates are subsolar for all major element/Si ratios but exhibit wide heterogeneity. This is not influenced by silicon oil from the capturing process of IDPs as assumed before, as a penetration of the silicon oil is excluded by high resolution EELS (electron energy loss spectroscopy) areal density maps of silicon. Furthermore, low Fe-content in GEMS amorphous silicates shows that these are not altered by aqueous activity on the parent body as it is the case for amorphous silicate material in primitive meteorites. The subsolar element/Si ratios and the wide chemical heterogeneity point to a non-equilibrium fractional condensation origin either in the early solar nebula or in a circumstellar environment and are not in agreement with homogenization via sputtering in the ISM. The close association with carbon around GEMS subgrains and as double-rims around GEMS aggregates argue for a multi-step aggregation after formation of the smallest GEMS subgrains in the ISM or the early solar nebula. Carbon acting as matrix material connecting GEMS and other IDP components has lower areal density as seen from carbon EELS areal density maps and isotopic anomalies varying at the nanometer scale, pointing to different origins and processing of materials to varying extent or at changing temperatures. To balance GEMS’ subsolar element/Si ratios, a supersolar component in IDPs was assumed to account for the overall chondritic composition of bulk IDPs. Nevertheless, our bulk IDP analyses revealed subsolar, but variable, element/Si ratios for complete particles as well, depending on type and amount of mineral phases in each particle. Pyroxenes in the investigated particles can occur as elongated euhedral crystals, but are overall rare. The dominant crystalline fraction in the investigated IDP samples are equilibrated aggregates (EAs) that show the same chemical compositions as GEMS, indicating that the EAs are recrystallized GEMS grains and formed after GEMS formation as secondary phases.